Analysis of Kamal al-din Esfahani’s Personal Style and Its Impact on Iraqi Style and Hindi Style of Poetry - seyyed mehdi tabatabaei (تاریخ ادبیات)
Researchers’ emphasis on Kamal al-din Esfahani’s style indicates the fact that his poetry heralds a change in the stylistics of the Persian poetry. A brief survey of the history of Persian Literature attests to the fact that a considerable number of poets pursued his poetic style. Through a brief survey of Esfahani’s poetic anthology and an overall review of antecedent critics, the present study recognizes the role of Esfahani’s personal style in the development of Persian poetry. The methodology of the present study is descriptive-analytical and the documentary method is utilized as the study’s data compilation tool. As a result, other scholars’ and critics’ findings have also been used in the study. The significance of the study lies in the importance of reviewing Kamal al-din Esfahani’s key role in Persian poetry. Furthermore, lack of a comprehensive study regarding Esfahani’s poetry makes the materialization of the present study more important. His role in Persian poetry should be studied through analysis of his personal style. It needs to be noted that some elements of his style have influenced Iraqi Style and Hindi Style of poetry, while other elements have remained without imitation in Persian poetry.